A mediação no ensino-aprendizagem de inglês para crianças: o papel do lúdico - Dellova, Cristiane Castelani (2009)
This dissertation aimed at investigating play in the classroom and its role in allowing changes in the mediational pattern in the context of teaching-learning of English to children. Its theoretical framework is the Social-Historical-Cultural Activity Theory (TASCH) with the discussions of concepts by Vygotsky (1930/1998, 1930/2003, 1934/2001, 1934/2004), Leontiev (1977, 1978), Engeström (1999) among others, in reference to activity-consciousness, teaching-learning, mediation and zone of proximal development. It is based on the studies of Bakhtin (1930/2006), Wertsch (1998), Orsolini (2004/2005) among others to understand how students appropriate of knowledge about the English language in the relationships with the teacher and colleagues in the classroom. To understand questions related to play, this study is also based on the discussions of Vygotsky (1930/1998), Elkonin (1978/1998), Leontiev (2006) and Newman & Holzman (2002), among others. To the data analysis and interpretation, the concepts of thematic content, person linguistic marker and modalizations by Bronckart (1997/2007), the quantitative/qualitative turn analysis through the creation of analysis categories based on the texts by Orsolini (2004/2005), Wertsch & Smolka (1993), Bakhtin (1986), Brookfield & Preskill (2005) and Kerbrat-Orecchioni (1996/2006) were used. This study was carried out in a language institute located in the city of Santo André, in a private teaching school throughout two months. The study followed a critical line of inquiry realized through a collaborative research (Magalhães 2007). Classes were recorded in which students took part in playful activities and the analysis indicated how the introduction of play in the classes and the sharing of meanings provided more comprehensive contexts for teaching-learning of English. The results presented here show that the change in the mediational pattern allowed not only the appropriation of the English language but also the transformation of the context under investigation, leading to new interpersonal relationships among the participants and a new vision of Teaching-Learning of English. They also pointed out a non-competitive learning environment in which there is respect and joint participation among the participants leading to a shared object - Teaching-Learning of English